Marauder elite intermediate hurdling - Thorson, M. (Track Coach, 2019)
The 400-meter hurdle race for men and women is the most demanding of the hurdle-sprint events. It requires a combination of speed endurance and hurdling skills to go along with a planned and unique stride pattern that demands a very special focus throughout the onelap race. The race consists of 10 hurdles placed 35 meters apart with a 45-meter run to the first barrier and a 40-meter run-in. The hurdle heights are 91.5 cm (36") for men and 76.0 cm (30") for women. The difficulty in the race comes from a large margin for error which is minimized by adopting and rehearsing a specific race plan that meets all situations. The necessary qualities for a successful, elite 400-meter hurdler include: 1. KINESTHETIC ABILITY-The athlete must have the ability to modify and adapt the race plan due to weather, lane assignment and prior technical issues during the course of the race. 2. RACE PLAN-A definite race plan with the correct pattern, pace, and 200-meter differentials must be trained. 3. SKILL-The required hurdling skills must be trained, with the hurdler training to competently hurdle with either leg. 4. SPECIAL ENDURANCE 1 AND 2-The athlete must be trained as a sprinter with the ability to perform very well in the flat 200- and 400-meter events. There are also elite 400 hurdlers who are very competent in the 600 meters and above and carry out a modified middle distance training schedule.